2020
DOI: 10.1186/s13098-020-00598-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and the incidence of lung cancer: a meta-analysis of cohort studies

Abstract: Background Metabolic syndrome (MetS) has been related to the pathogenesis of variety categories of cancers. This meta-analysis aimed to determine the association between MetS and the incidence of lung cancer. Methods Relevant cohort studies were identified by search of PubMed, Embase, and Cochrane’s Library databases. Cochrane’s Q test and I2 statistic were used to analyze the heterogeneity. Random-effect model which incorporates the potential heterogeneity was used for the meta-analysis. Results Five coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…While MS has multiple definitions, the most widely recognised criteria to construct MS belong to the NCEP ATP III and the IDF [1]. A study by Qiao et al found similar results when comparing NCEP ATP III and IDF criteria for the association between MS and lung cancer [41,42]. In contrast, Xiang and colleagues found that MS was a risk factor for breast cancer following IDF criteria, whereas no statistical association could be established using NCEP ATP III criteria [39].…”
Section: Plos Onementioning
confidence: 99%
“…While MS has multiple definitions, the most widely recognised criteria to construct MS belong to the NCEP ATP III and the IDF [1]. A study by Qiao et al found similar results when comparing NCEP ATP III and IDF criteria for the association between MS and lung cancer [41,42]. In contrast, Xiang and colleagues found that MS was a risk factor for breast cancer following IDF criteria, whereas no statistical association could be established using NCEP ATP III criteria [39].…”
Section: Plos Onementioning
confidence: 99%
“… 23 However, previous studies have shown that MS did not affect the morbidity, survival, or outcomes of lung cancer. 13 , 24 In our further 8-group exploration, we found that more than one metabolic abnormality was a risk factor for readmission risk in patients with lung cancer. If metabolic abnormality was regarded as comorbidity, consistent with our view, Zhu et al would show that the readmission risk in patients with lung cancer who combined with comorbidities was significantly higher and the readmission risk increased with the number of comorbidities.…”
Section: Discussionmentioning
confidence: 79%
“…12 However, other reports indicated that MS didn't increase the risk of lung cancer. 13 Considering these contradictory opinions, it seems to be more fitting to consider overweight/obesity or metabolic status separately or in combination to identify novel risk factors for readmission in patients with lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent studies showed that the association between MetS and cancers may be different according to the site of the cancer (15). For example, MetS has been related to increased risks of colorectal cancer (16), esophageal cancer, pancreatic cancer (17), breast cancer (18), endometrial cancer (19), and prostate cancer (20), but not to the risks of lung cancer (21) and gastric cancer (22). Although some studies have also evaluated the association between MetS and RCC (23)(24)(25)(26)(27)(28)(29)(30), the results were not consistent and it remains unknown whether MetS is independently associated with the incidence of RCC.…”
Section: Introductionmentioning
confidence: 99%